Indigenous archaeologies : decolonizing theory and practice - Smith, Claire, 1957-; Wobst, Hans Martin, 1943- (Routledge, 2005)
With case studies from North America to Australia and South Africa and covering topics from archaeological ethics to the repatriation of human remains, this book charts the development of a new form of archaeology that is informed by indigenous values and agendas. This involves fundamental changes in archaeological theory and practice as well as substantive changes in the power relations between archaeologists and indigenous peoples. Questions concerning the development of ethical archaeological practices are at the heart of this process.
Keywords: Ethnoarchaeology.; Social archaeology.; Indigenous peoples -- Antiquities.; Archaeology -- Philosophy.; Archaeologists -- Professional ethics.; Archaeology -- Fieldwork.; Human remains (Archaeology) -- Repatriation.; Cultural property -- Repatriation.; Ethnoarchéologie.; Archéologie sociale.; Autochtones -- Antiquités.; Archéologie -- Philosophie.; Archéologues -- Déontologie.; Archéologie -- Recherche sur le terrain.; Restes humains (Archéologie) -- Rapatriement.; Patrimoine culturel -- Restitution.; ethnoarchaeology.; SOCIAL SCIENCE -- Archaeology.; Indigenous peoples -- Antiquities; Archaeologists -- Professional ethics; Archaeology -- Fieldwork; Archaeology -- Philosophy; Cultural property -- Repatriation; Ethnoarchaeology; Human remains (Archaeology) -- Repatriation; Social archaeology; Ethnoarchäologie; Ethnoarchéologie -- Congrès.; Archéologie sociale -- Congrès.; Autochtones -- Antiquités -- Congrès.; Archéologie -- Philosophie -- Congrès.; Archéologues -- Déontologie -- Congrès.